2011
DOI: 10.1007/s11746-011-1814-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Portable Handheld Infrared Spectrometer for Quantitation of trans Fat in Edible Oils

Abstract: Trans fat poses serious health risks to consumers. In order to meet the FDA labeling requirements for trans fatty acids, development of fast, accurate, easy-to-use analytical methods for oils, fats and related products is desirable. Fourier transform infrared spectroscopy (FTIR) is a well-established analytical technique for quantifying trans fats, and the development of handheld FTIR units over the past decade presents new application opportunities. Our objective was to evaluate the performance of a handheld … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Because the timeliness has been more and more important for food quality control, the portable FTIR methods are required for the rapid and field assays of olive oils. Some hand-held FTIR spectrometers have been reported for the identification and parameter determination of edible oils (Allendorf et al, 2012;Aykas & Rodriguez-Saona, 2016;Birkel & Rodriguez-Saona, 2011;Li et al, 2008), but not used to screen the adulterated olive oils.…”
Section: Introductionmentioning
confidence: 99%
“…Because the timeliness has been more and more important for food quality control, the portable FTIR methods are required for the rapid and field assays of olive oils. Some hand-held FTIR spectrometers have been reported for the identification and parameter determination of edible oils (Allendorf et al, 2012;Aykas & Rodriguez-Saona, 2016;Birkel & Rodriguez-Saona, 2011;Li et al, 2008), but not used to screen the adulterated olive oils.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from the previous studies that the multivariate calibration approach combined with FTIR spectroscopy may improve the accuracy of determination of low TF levels 14,21 . To enhance spectral features, the second derivatives of absorption spectra were generated.…”
Section: Data Processing and Calibrationmentioning
confidence: 99%
“…To enhance spectral features, the second derivatives of absorption spectra were generated. Second derivative method was used for measured ATR-FTIR spectra with second order polynomial 21,22 . For each sample, peak…”
Section: Data Processing and Calibrationmentioning
confidence: 99%
“…The determination of trans FA in edible fats and oils including those with low trans FA concentrations, near or below 2 % of total FA, has been previously explored by FTIR [16,[19][20][21][22][23][24]36]. These infrared measurements were carried out in various single laboratory [19,[21][22][23][24]36] and multi-laboratory studies using single-bounce [23], multiple-bounce ATR-FTIR [16], and portable FTIR systems [16,36]. Precision data from the multi-laboratory collaborative study for AOCS Official IR Method Cd 14e-09 [19] indicated a 2 % limit of quantification for trans FA in edible fats and oils.…”
Section: Measurement Of Fat Extracts From Fast Food Samples With a Pomentioning
confidence: 99%